Exercise training decreases proinflammatory profile in Zucker diabetic (type 2) fatty rats - de Lemos, E. Teixeira (2015)
Objective: In the present study we evaluated the effect of exercise on the plasma levels of proinflammatory cytokines, interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha), and the anti-inflammatory molecule uric acid in the Zucker diabetic fatty (ZDF) rats that are more prone to develop type 2 diabetes mellitus. Methods: Sixteen obese ZDF(Gmi fa/fa) rats (8 wk old, 228.40 +/- 4.05 g) were randomly assigned to one of two groups (n = 8 each): an exercise-trained group and a sedentary one. In addition, 16 lean ZDF (Gmi +/+) rats (8 wk old, 199.00 +/- 3.50 g) were subjected to identical sedentary and exercise conditioning (n = 8 each). Initially, rats swam 15 min/d (5 d/wk) in a 36 degrees C bath. The exercise protocol was gradually increased by 15 min/d until a swimming period of 1 h/d (1 wk) was attained. Thereafter, rats swam 1 h/d, 3 d/wk, for an additional period of 11 wk. Rats were sacrificed 48 h after the last training period and the blood and pancreas were collected. Circulating levels of glucose, glycosylated hemoglobin, total cholesterol, triglycerides, insulin, uric acid, IL-6, and TNF-alpha were assessed. The concentrations of proinflammatory cytokines in the pancreas were also evaluated. Results: In the diabetic ZDF (fa/fa) rats, exercise decreased hyperuricemia (-37.3%) and IL-6 and TNF-alpha levels (-16.9% and -12.7% respectively) and maintained the weight of the pancreas at near normal. Immunohistochemistry revealed a marked decrease in the expression of TNF-alpha and IL-6 in the pancreatic islet cells of ZDF (fa/fa) rats. Conclusion: These results indicate that aerobic exercise is anti-inflammatory in nature. (C) 2009 Published by Elsevier Inc.. - Merck Sharp & Dohme Foundation, Portugal.. - This work was supported by a grant from Merck Sharp & Dohme Foundation, Portugal. U.N.D. received a Ramalingaswami Fellowship from the Department of Biotechnology, New Delhi, India, during the tenure of this study.